Pre-Service Teacher’s Perceptions of Disainary for Learning English Scientific Vocabulary: A Qualitative Study - Lucky Amatur Rohmani Rohmani; Luthfi Awwalia; Anis Zahrotin (Faculty of Education and Teacher Training of UIN Palopo, 2026)
The globalization of science has reinforced English as the dominant language of scientific communication, requiring pre-service science teachers to acquire sufficient mastery of English scientific terminology for academic and professional success. However, many pre-service teachers in Indonesia face persistent challenges, including limited vocabulary, low confidence, and insufficient access to effective learning media. To address these issues, digital tools such as Disainary, a multimodal web-based dictionary designed for scientific terms, have been introduced as innovative learning resources. This study aims to explore pre-service science teachers’ perceptions and experiences of using Disainary in vocabulary learning. Employing a descriptive qualitative design, data were collected through semi-structured interviews and classroom observations with 30 participants across several universities in Indonesia. This used purposive sampling technique to employ the participants. The findings indicate three major themes: (1) vocabulary acquisition through repetition and multimodality, (2) increased motivation and engagement, and (3) challenges and limitations. Participants highlighted that Disainary facilitated repeated encounters with scientific terms through definitions, contextual examples, and pronunciation features, which enhanced comprehension and retention. Moreover, the tool’s accessibility and scientific contextualization motivated learners to engage with vocabulary more actively. Despite these benefits, participants emphasized the need for expanded lexical coverage, additional exercises, and the visual elements to optimize learning. The study concludes that Disainary holds strong potential as a digital learning tool to bridge the gap between English vocabulary acquisition and science literacy in teacher education. Implications suggest that integrating multimodal digital tools can not only enhance pre-service teachers’ language proficiency but also prepare them for effective knowledge transmission in globalized science classrooms.